Differences in Banking Financial Performance Before and After the Implementation of PSAK 71 (Empirical Study on Banking Companies Listed on the IDX in 2018-2021) - Nuha, Achmad Ulin; Zuhrohtun, Zuhrohtun; Prasetio, Januar Eko (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
A bank is an entity that manages public funds and must ensure that its financial information reflects comprehensive and high-quality data. In financial accounting, the quality of financial information is indicated by its usefulness. The quality of financial information can be assessed from two perspectives: the quality related to the overall performance of the entity, as manifested in sustainable profits, and the quality related to capital market performance. The purpose of this study is to analyze the differences in Allowance for Impairment Losses on Credit before and after the implementation of PSAK 71, analyze the differences in the Capital Adequacy Ratio (CAR) before and after the implementation of PSAK 71, and analyze the differences in Return on Assets (ROA) before and after the implementation of PSAK 71. The results of the study indicate that (1) there is a significant effect of the implementation of PSAK 71 on Total Allowances for Credit in the periods 2018-2019 and 2020-2021, (2) there is a significant effect of the implementation of PSAK 71 on CAR in the periods 2018-2019 and 2020-2021, (3) there is a significant effect of the implementation of PSAK 71 on ROA in the periods 2018-2019 and 2020-2021, and (4) there is no significant difference in SIZE between the periods 2018-2019 and 2020-2021.